Street Forró Pé-de-Serra in Rio de Janeiro: Between traditions and cultural hybridizations (Intercom - Brazilian Journal of Communication Sciences, 2026)
Following the trails of the actors of Rio de Janeiro's street forró pé-de-serra throughout 2024 and 2025, we aimed to analyze the partial results of empirical work carried out within this music scene which involved field observations, interviews, informal conversations, and monitoring of posts and articles published in traditional media and social media. Overall, in light of the controversies among the various actors, our corpographic and cartographic approach sought to rethink the relevance of musical activities performed in person, especially in public spaces by artists and collectives—in sonic-musical territorialities that gravitate around regularly held concerts and balls—which promote processes of urban resignification relevant to everyday life. In short, we seek to assess how these initiatives help transform these territories into more plural and socially inclusive environments.
Keywords: Communication; Culture; Music; Tradition; Politic